(untitled) (Canadian Oncology Today, 2024)
In Canada, 92% of colorectal cancer cases occur in patients over 50 years of age. Accordingly, most colorectal cancer research and early-detection efforts have traditionally focused on older Canadians. However, the epidemiology of colorectal cancer in Canada is changing. Over the past three decades there has been a substantial decrease in the incidence of colorectal cancer among patients over age 50 but an alarming increase in the incidence among patients under 50. It is estimated that by 2040 colorectal cancer will be the leading cause of cancer‑related death for individuals aged 20–49. This paper will provide a broad overview of the unique characteristics and care needs affecting patients with early age onset colorectal cancer (EAOCRC) from a Canadian perspective. Unless otherwise specified, EAOCRC will refer to individuals diagnosed with colorectal cancer under age 50.